ANALISIS BIBLIOMETRIK FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN PENALARAN MATEMATIS SISWA - Khairunnisa Khairunnisa; Hasanuddin Hasanuddin (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to map the research landscape regarding the factors that affect students' mathematical reasoning skills through bibliometric analysis. Data on scientific publications indexed in Google Scholar in the range of 2020 to 2025 were analyzed using the Publish or Perish application for data collection and VOSViewer for network visualization and keyword clusters. A total of 481 documents were identified and analyzed to identify publication trends, research focuses, and relationships between concepts. The results show a significant increase in the volume of publications related to this topic during the period, with the main focus of the research on "mathematical reasoning skills" and "mathematical learning". Network visualization analysis identified seven main clusters representing different research areas. In addition, this study highlights the lack of research that explicitly raises the topic of "critical thinking" in the context.